Faktor-Faktor yang Mempengaruhi Kejadian Pedikulosis Kapitis pada Murid Kelas III, IV, V Dan VI SDN 019 Tebing Tinggi Okura Kecamatan Rumbai Pesisir Pekanbaru - Aprilia Zulinda; Yolazenia Yolazenia; Zahtamal Zahtamal (Fakultas Kedokteran Universitas Riau, 2010)
Pediculosis capitis disease spread on to the whole world and found mostly in people with low in hygiene and socioeconomic.This Pediculosis capitis could be found in all age people especially in student age. The purpose of thisresearch was to know description the factors that affect Pediculosis capitis case in IIIrd, IVth, Vth and VIth graders ofSDN 019 Tebing Tinggi Okura in Rumbai Pesisir subdistrict of Pekanbaru. This cross sectional research had beendone in March until August 2009 period. Sampel examination was done in macroscopicaly using serit comb to find thelouse eggs and mature louses. From this study, 53 (39,3%) of 135 sampel student were infected by Pediculus humanuscapitis. Based on data analyses, there were known that sex, hair length, parents education, social and economicalcondition of the family, hair washing frequence, using tools related to hair together and comb cleaning custom variableshad significant relation that affect Pediculosis capitis (p<0,05).